Effect of TiF4 varnish in the prevention and remineralization of caries lesions in permanent teeth of children living in a fluoridated region: randomized clinical trial of 18 months - Souza, Beatriz Martines de (2019)
This randomized-controlled clinical trial compared the effect of TiF4 and NaF varnishes in the treatment of non-cavitated caries lesions and in the prevention of new lesions in permanent teeth. Sixty children (6-7 y/o) from 5 municipal schools of Bauru-SP (Brazil), according to the caries activity (at least 1 active white spot lesion), were selected and randomly divided into the following treatments (varnishes): 4% TiF4 (2.45% F-, FGM); 5% NaF (2.26% F-, Duraphat®-Colgate) or placebo (without F-, FGM). Varnishes were applied on permanent teeth, once a week (4 weeks); after the 6th and 12th month. Clinical examination (Nyvad/ICDAS) and quantitative fluorescence changes analysis (QLF) were performed after 1 month of the treatment and after 6, 12 and 18 months after the beginning of the study. Patients satisfaction degree was reported after each varnish application by visual scale. Visual plaque index (VPI) was calculated and measured after the 3rd, 9th and 15th months. The 1st paper of this thesis was published in the JMIR Research Protocols showing the experimental design model. Two-way RM-ANOVA, ANOVA/Tukey and 2 were performed. No differences were found between treatments with respect to carious lesions regression/progression using Nyvad/ICDAS (p>0.05). Only TiF4 varnish was able to reduce the mean fluorescence loss significantly after 18 months (-14.6 ± 4.0%) compared to the baseline value (-17.5 ± 3.9%, p=0.003). Regarding the prevention of new lesions, only TiF4 (99.2 ± 1.7%) presented a significantly higher percentage of sound surfaces at the end of the 18 months compared to placebo (94.9 ± 7.9%), while the NaF did not differ from the two groups (98.5 ± 2.1, p=0.014%). Around 97% of the participants reported being satisfied with treatments, regardless of varnish. The VPI percentage decreased significantly after 9 and 15 months compared to 3 months (p<0.001). TiF4 varnish was the only treatment able to show beneficial effect under this study model. The 2nd article of this thesis showed the results and it will be sent to the International Journal of Paediatric Dentistry.